The reception of María de Zayas in nineteenth‐century Britain - Medina Calzada, Sara (Orbis litterarum, 2025)
This article examines the reception of the Spanish novelist María de Zayas (1590–after 1647) in nineteenth‐century Britain. At the time, Spanish literature gained visibility and reputation in Britain, especially during the Romantic period and the last decades of the century, but attention tended to focus on male writers. Zayas, whose novellas had circulated in English translation between the 1660s and the 1770s without being attributed to her, was one of the few Spanish women authors who attracted the interest of British critics and translators back then. There are references to her in several critical pieces and studies of Spanish literature, and two of her novellas were translated into English: El castigo de la miseria , which was included in Thomas Roscoe's The Spanish Novelists (1832), and El jardín engañoso , which was published in The Parlour Magazine (1851). Although Zayas started to be recognized as a novelist in the incipient British Hispanism of the time, her works were mostly considered indecent or at least nonconformant to nineteenth‐century British values and morals.